Preliminary report of the toxicity of Lippia junelliana (Lamiales: Verbenaceae) and Elionorus muticus (Poales: Poaceae) on Apis mellifera (Hymenoptera: Apidae) - Vega, Maricel (2022)
Several phytochemicals, such as extracts and essential oils, are among the ecological alternatives that have been studied for the control of pathogens that affect humans, animals, and plants. Essential oils are aromatic oily liquids obtained from plant material and their use to control pathogens is widespread. However, they can have adverse effects when taken in high concentrations. The aim of this study was to evaluate the survival and palatability of a balanced-energy protein diet with the addition of two essential oils, Lippia junelliana (Mold.) Tronc. and Elionorus muticus (Spreng.) Kuntze, in newly hatched worker bees (Apis mellifera L.) during a period of 15 days. Consumption and number of live bees were measured daily for each treatment. For L. junelliana, our results showed a non-toxic trend in long-term survival trials (15 days) at low concentrations. In the case of E. muticus, a toxic effect with low survival was observed at all concentrations. Both essential oils showed good palatability, even at toxic levels. Our results allow us to propose the use of L. junelliana essential oil in field experiments of A. mellifera hives.